2015
DOI: 10.3748/wjg.v21.i29.8836
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of nemo-like kinase is an independent prognostic factor in colorectal cancer

Abstract: NLK overexpression is an independent prognostic factor in colorectal cancer and knockdown of NLK expression inhibits colorectal cancer progression and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…For instance, Zhu et al, found that Twist1 could enhance proliferation and chemoresistance of CRC cells which might be a potential prognostic marker and a molecular therapeutic target for the cancer [21]. Zhang et al indicated that up-regulation of nemolike kinase (NLK) was positively correlated with recurrence and distant metastasis of CRC patients, predicting poor prognosis for patients with the disease [22]. The clinical signi cance of MTA2 expression for prognosis of CRC was investigated by Ding et al They found the expression pro le of MTA2 exhibited high in CRC tissues specimens, and signi cantly correlated with overall survival of the patients, suggesting its possible as a prognostic biomarker for CRC [23].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhu et al, found that Twist1 could enhance proliferation and chemoresistance of CRC cells which might be a potential prognostic marker and a molecular therapeutic target for the cancer [21]. Zhang et al indicated that up-regulation of nemolike kinase (NLK) was positively correlated with recurrence and distant metastasis of CRC patients, predicting poor prognosis for patients with the disease [22]. The clinical signi cance of MTA2 expression for prognosis of CRC was investigated by Ding et al They found the expression pro le of MTA2 exhibited high in CRC tissues specimens, and signi cantly correlated with overall survival of the patients, suggesting its possible as a prognostic biomarker for CRC [23].…”
Section: Discussionmentioning
confidence: 99%
“…They aid in metabolism and nutrient availability by fermenting complex carbohydrates into short-chain fatty acids (SCFA), which can be used as an energy source by mucosa. Bacteria can also produce vitamins, such as vitamin K and components of certain vitamin B species ( 17 ), and play a role in the metabolism of medications. Gut microbiota also aid in the protection against pathogens by competitive exclusion ( 16 , 17 ).…”
Section: Key Players Of the Human Gut Microbiotamentioning
confidence: 99%
“…Bacteria can also produce vitamins, such as vitamin K and components of certain vitamin B species ( 17 ), and play a role in the metabolism of medications. Gut microbiota also aid in the protection against pathogens by competitive exclusion ( 16 , 17 ). The tremendous contribution of bacteria to host physiology is best seen in germfree (GF) mice, which have impaired development of the epithelium, musculature, and vasculature of the intestines as well as systemic defects, such as in immune functions and brain development.…”
Section: Key Players Of the Human Gut Microbiotamentioning
confidence: 99%
See 2 more Smart Citations